Immunocompetent young man with cerebral abscess and cortical venous infarction mimicking cerebritis caused by Gemella morbillorum. (25th January 2013) - Milnik, Annette; Gazis, Angelos; Tammer, Ina; Bartels, Claudius
Abstract : Gemella morbillorum is an anaerobic gram-positive diplococcus and in most cases a harmless commensal, which occasionally causes infections in the central nervous system. We report on an immunocompetent young man with focal neurological symptoms and cephalgia caused by a cerebral abscess. Although successful treatment was done with neurosurgical intervention and antibiotic therapy, he suffered from a venous infarction 5 weeks after first diagnosis, which mimicked cerebritis as an early stage of relapsing abscess. Imaging and investigation of cerebrospinal fluid was necessary for sufficient differential diagnosis and antibiotic therapy could be stopped after altogether 8 weeks of treatment. In summary, G morbillorum causes not only biphasic infections, but also can be accompanied by infarction in the central nervous system despite sufficient antibiotic therapy.